ONLINE AND INTERNET GAMES AGAINST DISCIPLINE MINDSETS AND PRODUCTIVE PROCESSES IN IMPROVING HUMAN RESOURCES FOR STUDENTS - Widjanarko, Wirawan (Jurnal Ekonomi, 2022)
Internet and Online Games are technologies that are widely used by every human being, and with the rapid development of technology it can affect humans or society as users of these technologies, which ends up causing negative and positive impacts depending on the use of the technology itself, for example if it is not wise. In its use it will cause laziness, lack of discipline, not developing a mindset and can hinder productive activities that should be carried out. So that this can affect the improvement of Human Resources itself, especially for students. The method used is quantitative data in the form of primary data where the data is generated based on the distribution of questionnaires to students, both male and female, who use the internet and play online games. This data is processed using Smart Pls Software. The equation model analyzed is the Outer Model, Inner Model and Hypothesis testing, based on calculations using the software produces the relationship between the Internet and Online Games on Discipline, Mindset and Productive Processes in order to increase Human Resources for students.